One-year operation of 1000-L modularized microbial fuel cell for municipal wastewater treatment - Liang, Peng; Duan, Rui; Jiang, Yong; Zhang, Xiaoyuan; Qiu, Yong; Huang, Xia (Water research (Oxford), 2018)
This study constructed a 1000 L modularized MFC system, the largest volume so far, to treat practical municipal wastewater. This MFC system was operated under two different water flow connections in two municipal wastewater treatment plants (MWTP) for more than one year to test their treating abilities for wastewater with both low (average 80 mg L−1) and high initial COD concentration (average 250 mg L−1). The COD concentration in the effluent from the MFC system remained below 50 mg L−1 with a removal rate of 70–90%, which stably met the level A of the first class in discharge standard of pollutants for MWTP of China. A maximum power density of 125 W m−3 (7.58 W m−2) was generated when the MFC system was fed with artificial wastewater, while it lay in a range of 7–60 W m−3 (0.42–3.64 W m−2) when treating municipal wastewater. The energy recovery of 0.033 ± 0.005 kWh per m3 of municipal wastewater was achieved, with a hydraulic retention time (HRT) of 2 h. [Display omitted] •Scaled-up (1000 L) MFC consisted of 50 modules was operated for a year.•The MFC was applied to treat artificial and real municipal wastewater.•Concentration of COD released was below 50 mg L−1 with a removal rate of 70–90%.•The maximum power density harvested from municipal wastewater was 7–60 W m−3.